Development of Science Module Based on Scientific Approach to Improve Science Process Skills of Elementary School Students - Dini Puji Anggraini; Riskyka Riskyka (Pedagogik Journal of Islamic Elementary School, 2023)
This research aims to develop a science module based on a scientific approach to improve science process skills. This research is research and development. This research uses ADDIE development model which has 5 stages, namely analysis, design, development, implementation, and evaluation. This research only reached the implementation stage. The research was carried out at Hamas IT Elementary School. The research subjects were 18 class VI students. The object in this research is VIscience module based on a scientific approach. Data collection techniques are observation, interviews, questionnaires, tests. Data analysis in research is: (a) feasibility analysis science module based on a scientific approach and (b) effectiveness analysis science module based on a scientific approach. Based on the validation results for the product developed, namely a science module based on a scientific approach, show that the material expert validation results are 94.56%, including the very feasible category. Meanwhile, the results of media expert validation, namely 88.70% included in the very worthy category. The results of the pretest that were carried out showed that only 1 student completed it and 17 students did not complete it with a percentage of 44%. Meanwhile, the results of the posttest that had been carried out showed that 18 students completed the test with a percentage of 78%. Based on the explanation above, it can be concluded that the scientific approach based science module developed is suitable and effective for use by sixth grade students at Hamas IT Elementary School.